Attenuation of sepsis-induced myocardial injury by Xiangdan injection via mitochondrial protection and inflammation suppression in mice - Chang, Yuejin; Zhang, Wenlei; Pan, Jinbo; Lin, Zhenhao; Bai, Hongxia; Li, Hui (Frontiers in Medicine, 2025)
BackgroundSepsis-induced myocardial injury (SIMI) is a leading cause of organ dysfunction and mortality in septic patients. Effective myocardial-protective therapies remain limited.ObjectiveThis study evaluated the cardioprotective effects of Xiangdan injection in murine SIMI models caused by both Gram-positive and Gram-negative bacteria.MethodsMale C57BL/6 mice were assigned to sham, sepsis, and three Xiangdan dose groups for each bacterial model using a randomization schedule. Xiangdan injection was administered by oral gavage 12 h before and immediately after bacterial challenge (prophylaxis/early intervention). Outcomes included survival, serum inflammatory cytokines, cardiac biomarkers, histopathology, and ultrastructural mitochondrial integrity.ResultsXiangdan injection markedly improved survival, reduced inflammatory cytokines and cardiac biomarkers, ameliorated myocardial histopathology, and preserved mitochondrial integrity in a dose-dependent manner in both sepsis models (P < 0.05).ConclusionXiangdan injection conferred robust cardioprotection in sepsis, combining anti-inflammatory effects, reduction of cardiac injury markers, and preservation of mitochondrial structure. These outcomes are consistent with the known capacity of traditional Chinese medicine formulations to modulate TLR4/NF-κB and JAK2/STAT3 pathways, thereby supporting mechanistic suppression of these cascades in our model.